Quintessence or phantom: Study of scalar field dark energy models through a general parametrization of the Hubble parameter - Nandan Roy (2022)
In this work we propose a simple general parametrization scheme of the Hubble parameter for the scalar field dark energy models. In our approach it is possible to incorporate both the quintessence and phantom scalar field in a single analytical scheme and write down relevant cosmological parameters which are independent of the nature of the scalar field. A general condition for the phantom barrier crossing has also been obtained. To test this approach, a well behaved parametrization of the normalized Hubble parameter has been considered and a wide variety of observational data like CMB data, Supernovae data, BAO data etc. has been used to constraint the various cosmological parameters. It has been found that data prefer the present value of the equation of state of the dark energy to be in the phantom domain. One interesting outcome of this analysis is that although the current value of the dark energy equation of state is phantom in nature, a phantom crossing of the EOS has taken place in the recent past. We have also carried out the Bayesian model comparison between ΛCDM model and the proposed model which indicates that this model is favored by data as compared to ΛCDM model.